Analysis of crafts (Kriya) creative industries: a case study of policy development in Banten Indonesia - Muhtarom Muhtarom; Moh Sofyan Budiarto; Sugeng Setyadi; Muhlisin Muhlisin; Yunia Rahayuningsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study analyzes the development of a leading sector in the creative industry in Banten Province, namely Kriya or Craft. The study used a qualitative descriptive method by conducting a survey of creative industry players in Banten province. Primary data is obtained by interviews and questionnaires while secondary data is obtained from relevant data, literature, and other sources. Data analysis using SWOT to determine the factors of strength, weakness, opportunities, and threats based on the selected indicators. After the measurement of strength, weakness, threat, and opportunity were obtained then entered into the EFAS and IFAS Matrix table by scoring each identified factor. The results of the study showing the position of the Craft Industry based on local potential in Banten Province depend on cell 5a (2.04; 2.47) so that the strategy taken is a stable growth (Growth) strategy, namely concentration through horizontal assistance. Provincial governments can integrate horizontal strategies in the development of the creative economy through 1) Regional policy for sustainable craft creative industry development; 2) Optimizing HR capacity and assets; 3) Improving market access for crafts (kriya) products; 4) Conducting training that focuses on continuity and on target; 5) Improving the mindset of creative industry player; 6) Developing a pattern of partnership cooperation.